Spatiotemporal Transcriptome Analysis Provides Insights into Bicolor Tepal Development in Lilium “Tiny Padhye” - Xu, Leifeng; Yang, Panpan; Feng, Yayan; Xu, Hua; Cao, Yuwei; Tang, Yuchao; Yuan, Suxia; Liu, Xinyan; Ming, Jun (Frontiers in Plant Science, 2017)
The bicolor Asiatic hybrid lily cultivar ‘Tiny Padhye’ is an attractive variety because of its unique color pattern. During its bicolor tepal development, the upper tepals undergo a rapid color change from green to white, while the tepal bases change from green to purple. However, the molecular mechanisms underlying these changes remain largely uncharacterized. To systematically investigate the dynamics of the lily bicolor tepal transcriptome during development, we generated 15 RNA-seq libraries from the upper tepals (S2-U) and basal tepals (S1-D, S2-D, S3-D, and S4-D) of Lilium ‘Tiny Padhye’. Utilizing the Illumina platform, a total of 295,787 unigenes were obtained from 713.12 million high-quality paired-end reads. A total of 16,182 unigenes were identified as differentially expressed genes during tepal development. Using Kyoto Encyclopedia of Genes and Genomes pathway analysis, candidate genes involved in the anthocyanin biosynthetic pathway (61 unigenes) and chlorophyll metabolic pathway (106 unigenes) were identified. Further analyses showed that most anthocyanin biosynthesis genes were transcribed coordinately in the tepal bases, but not in the upper tepals, suggesting that the bicolor trait of ‘Tiny Padhye’ tepals is caused by the transcriptional regulation of anthocyanin biosynthetic genes. Meanwhile, the high expression level of chlorophyll degradation genes and low expression level of chlorophyll biosynthetic genes resulted in the absence of chlorophylls from ‘Tiny Padhye’ tepals after flowering. Transcription factors putatively involved in the anthocyanin biosynthetic pathway and chlorophyll metabolism in lilies were identified using a weighted gene co-expression network analysis and their possible roles in lily bicolor tepal development were discussed. In conclusion, these extensive transcriptome data provide a platform for elucidating the molecular mechanisms of bicolor tepals in lilies and provide a basis for similar research in other closely related species.